FUTURE DIRECTIONS OF THE CURRENT TOCOLYTIC THERAPY AS A PART OF COMBINATION THERAPY FOR THREATENED PRETERM LABOR (LITERATURE SURVEY) - Y. E. Dobrochotova; A. V. Van; A. S. Culicova (IRBIS LLC, 2016)
An analysis of literature data is given regarding the role of different types of therapy used for the treatment of threatened preterm labor including the efficacy and safety of such treatments.